2014
DOI: 10.1002/hbm.22655
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity and neuronal variability of resting state activity in bipolar disorder—reduction and decoupling in anterior cortical midline structures

Abstract: These findings suggest that in BD the communication, that is, information transfer, between the different cortical midline regions within the cingulate gyrus does not seem to work properly. This may result in dysbalance between different resting state networks like the DMN and SN. A deficit in the anterior DMN-SN connectivity could lead to an abnormal shifting toward the DMN, while a deficit in the anterior DMN-posterior DMN connectivity could lead to an abnormal shifting toward the SN, resulting in excessive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
69
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(80 citation statements)
references
References 56 publications
6
69
1
Order By: Relevance
“…Accordingly, major functional and structural alterations were found in the anterior DMN (17,(19)(20)(21). The ultraslow frequency band, Slow5, was interestingly found to be more dominant, especially in the ventromedial prefrontal cortices; that is, the anterior cortical midline structures, which are central to the DMN (35,56).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Accordingly, major functional and structural alterations were found in the anterior DMN (17,(19)(20)(21). The ultraslow frequency band, Slow5, was interestingly found to be more dominant, especially in the ventromedial prefrontal cortices; that is, the anterior cortical midline structures, which are central to the DMN (35,56).…”
Section: Discussionmentioning
confidence: 94%
“…Resting-state networks and their relationships have been investigated in BD by using functional connectivity (FC) (17)(18)(19)(20)(21), which provides information on the spatial structure of neural networks, importantly contributing to a better understanding of the relationship between the activity of different brain regions and how they interact via networks in different states (35). In addition to FC, which mainly targets the spatial dimension, the variability of the amplitude of neural activity, which implies a strong temporal dimension, has recently been investigated to characterize the resting state in the healthy brain (36)(37)(38)(39)(40).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…For example, Pavuluri et al (69) found that secondgeneration antipsychotics showed enhanced prefrontal and temporal lobe activity in patients with adolescent BD. These deficits have promise as potential biomarkers in the clinical diagnosis of and treatment planning for BD (70).…”
Section: Attention Deficit Hyperactivity Disordermentioning
confidence: 99%
“…For example, Pavuluri et al (69) found that secondgeneration antipsychotics showed enhanced prefrontal and temporal lobe activity in patients with adolescent BD. These deficits have promise as potential biomarkers in the clinical diagnosis of and treatment planning for BD (70 (Fig 5). We also found substantial alterations in brain function that are similar in many ways to those observed in patients with PTSD in individuals shortly after major traumatic experiences, highlighting the need for a meta-analysis, which revealed that PTSD symptom severity was negatively correlated with gray matter in the left anterior cingulate cortex and positively correlated with gray matter in the left insula (89).…”
mentioning
confidence: 99%